Penerapan Model Problem Based Learning dengan Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar IPAS Peserta Didik Kelas VI B UPT SD Negeri 060913 Medan - Simarmata, Kiki Mewani; Mushlihuddin, Rahmat; Agustina, Fitri (LPPPI Publishing, 2025)
This study aims to improve the science learning outcomes of Grade VI B students at UPT SD Negeri 060913 Medan on the topic of the solar system through the implementation of the Problem Based Learning (PBL) model combined with the Teaching at the Right Level (TaRL) approach. The background of this study is the low learning outcomes and student participation, which are caused by the lack of variety in teaching methods and the failure to accommodate differences in levels of understanding. Students with varying abilities often do not receive learning treatment that suits their individual needs, resulting in difficulties in understanding the material. The subjects of this study consisted of 22 students. This research is a Classroom Action Research (PTK) conducted in two cycles, namely Cycle I and Cycle II. Each cycle consisted of the stages of planning, implementation of action, observation, and reflection. Data collection techniques were carried out using tests with question sheets and were analyzed by calculating the average scores and the percentage of classical completeness. The results of the study showed an improvement in learning outcomes from an average score of 74 with a completeness percentage of 64% in Cycle I to an average score of 89 with a completeness percentage of 91% in Cycle II. The findings indicate that the implementation of Problem Based Learning (PBL) with the Teaching at the Right Level (TaRL) approach is effective in improving students’ science learning outcomes and encouraging their active participation in the learning process.